까다로운 식습관과 식품수용에 영향을 미치는 요인 - 심재은(Jae Eun Shim) (동아시아식생활학회지, 2021)
Early childhood is an important period to establish food preference and acceptance through various experiences with food. Individuals have different food preferences and acceptance through the degree of exposure to foods with various flavors and textures, and through physiological, psychological, and emotional experiences related to food intake, partly depending on their temperament. Picky eating is a common eating problem that exhibits limited food acceptance in childhood. In this study, the factors related to food acceptance and specifically the factors influencing picky eating were reviewed. In particular, it followed an approach that classified picky eating according to the behavior type: a type of insufficient intake, which is eating small amounts; a type of insufficient intake diversity, which are neophobic behavior, refusal of specific food groups, and preference for specific food preparation methods. The factors influencing picky eating were explored. These included temperament, food neophobia, flavor & texture preference, taste and tactile sensitivity, physiological capacity, and insufficient and negative food experience during a sensitive period in food learning. The the eating environment provided by the caregiver determines the food experience of the child because the diet of early childhood is dependent on the caregiver. Therefore, caregivers should provide a food environment that supports healthy eating of their children by understanding the development of food preference and acceptance. KCI Citation Count: 0